A Survey for Comparative Analysis of various Security Methods to protect User Authentication on Cloud - Ms.Shweta Kiran Yande, Dr. Blessy Thankachan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Now-a-days there are many organization who have huge amount of data to be stored. This increases the demand for huge storage. Cloud storage is one of the solution to it. As the demand for the cloud storage is increasing, so is the security to keep data and user save is also increasing. The National Institute of Standards and Technology (NIST) defines cloud computing as “Cloud computing is a model for enabling ubiquitous, convenient,on-demand network access to a shared pool of configurable computing resources (e.g. networks, servers, storage, applications, and services) that can be rapidly provisioned andreleased with minimal management effort or service provider interaction”[Kumar et al., 2020].Through cloud computing data can be accessed by many users simultaneously, therefore proper identification and authentication of the user is mandatory. In this survey, comparative analysis of various technique used to authenticate the user over cloud is done.